The Banana Fruit SINA Ubiquitin Ligase MaSINA1 Regulates the Stability of MaICE1 to be Negatively Involved in Cold Stress Response - Fan, Zhong-Qi; Chen, Jian-Ye; Kuang, Jian-Fei; Lu, Wang-Jin; Shan, Wei (Frontiers in Plant Science, 2017)
The regulation of ICE1 protein stability is important to ensure effective cold stress response, and is extensively studied in Arabidopsis. Currently, how ICE1 stability in fruits under cold stress is controlled remains largely unknown. Here, we reported the possible involvement of a SEVEN IN ABSENTIA (SINA) ubiquitin ligase MaSINA1 from banana fruit in affecting MaICE1 stability. MaSINA1 was identified based on a yeast two-hybrid screening using MaICE1 as bait. Further yeast two-hybrid, pull-down, bimolecular fluorescence complementation (BiFC) and co-immunoprecipitation (CoIP) assays confirmed that MaSINA1 interacted with MaICE1. The expression of MaSINA1 was repressed by cold stress. Subcellular localization analysis in tobacco leaves showed that MaSINA1 was localized predominantly in the nucleus. In vitro ubiquitination assay showed that MaSINA1 possessed E3 ubiquitin ligase activity. More importantly, in vitro and semi-in vivo experiments indicated that MaSINA1 can ubiquitinate MaICE1 for the 26S proteasome-dependent degradation, and therefore suppressed the transcriptional activation of MaICE1 to MaNAC1, an important regulator of cold stress response of banana fruit. Collectively, our data reveal a mechanism in banana fruit for control of the stability of ICE1 and for the negative regulation of cold stress response by a SINA E3 ligase via the ubiquitin proteasome system.